Membangun Kembali Dialog Keagamaan: Telaah Deskriptif-singkat atas Ensiklik Fratelli Tutti Menurut Paus Fransiskus - Fransiskus Sulaiman Otor (Dekonstruksi, 2021)
Pope Francis is a pioneer in building religious dialogue in the contemporary era. The Pope recalled the events of the dialogue between Francis Assisi and Sultan Malik Al-Khamil in an atmosphere of brotherhood even in the midst of the Crusades (1219). Exactly 800 years later, he repeated a similar experience. He had a dialogue with Ahmad El-Tayeb, Grand Imam of Al-Azhar in Abu Dhabi (2019). There, the two signed the document “Human Brotherhood for World Peace and Living Together”. A year later, the Pope published the encyclical Fratelli Tutti (2020). Based on the concept of "Brotherhood and Social Friendship", he called for all people to join hands to fight for world peace. He urged that religious dialogue needs to be increased to the grassroots. This momentum in the international arena is a new milestone in the relations of Muslims and Christians, as well as having a major impact on the progress of dialogue between religious believers around the world.